Does deregulation induce competition in the market for corporate control? The special case of banking - Ghosh, Chinmoy; Petrova, Milena (Journal of Banking & Finance, 2013)
Using a sample of 936 acquisitions of commercial banks, we examine the relation between the probability to engage in value-reducing acquisitions and corporate governance structures, as well as the relation between acquirer announcement-period abnormal stock returns and antitakeover indices and measures, and how these relations were affected by the change in the market for corporate control, caused by deregulation due to the implementation of the Interstate Banking and Branching Efficiency Act of 1994 and the Financial Service Modernization Act of 1999. We find that prior to deregulation there is no relation between probability to engage in value destroying acquisitions or acquirer returns and antitakeover indices, whereas after the adoption of the FSMA, probability to engage in value destroying acquisitions and the stock market reaction to bidder M&A announcements are both significantly related to governance indexes and measures. Our findings further confirm the linkage between the market for corporate control, antitakeover indices and firm value.